Increasing Solar Absorption of Atomically Thin 2D Carbon Nitride Sheets for Enhanced Visible‐Light Photocatalysis. Issue 40 (22nd August 2019) - Wang, Yong; Du, Peipei; Pan, Hongzhe; Fu, Lin; Zhang, Yu; Chen, Jie; Du, Youwei; Tang, Nujiang; Liu, Gang
Abstract: Atomically thin 2D carbon nitride sheets (CNS) are promising materials for photocatalytic applications due to their large surface area and very short charge‐carrier diffusion distance from the bulk to the surface. However, compared to their bulk counterpart, CNS' applications always suffer from an enlarged bandgap and thus narrowed solar absorption range. Here, an approach to significantly increase solar absorption of the atomically thin CNS via fluorination followed by thermal defluorination is reported. This approach can greatly increase the visible‐light absorption of CNS by extending the absorption edge up to 578 nm. The modulated CNS loaded with Pt cocatalyst as a photocatalyst shows a superior photocatalytic hydrogen production activity under visible‐light irradiation to Pt‐CNS. Combining experimental characterization with theoretical calculations shows that this approach can introduce cyano groups into the framework of CNS as well as the accompanied nitrogen vacancies at the edges, which leads to both narrowing the bandgap and changing the charge distribution. This study will provide an effective strategy to increase solar absorption of carbon‐nitride‐based photocatalysts for solar energy conversion applications. Abstract : An approach of fluorination followed by thermal defluorination is used to narrow the bandgap of atomically thin 2D carbon nitride sheets for realizing a strong visible‐light absorption. The photocatalyst based on this material shows a much superior photocatalytic H2 evolution under visible‐light irradiation.